Pernikahan Beda Agama Perspektif Al-Qur’an - Jaini Jaini; Faisar Ananda Arfa (Peneliti.net, 2023)
Interfaith marriage is a phenomenon that is currently happening. It cannot be denied that the implementation of interfaith marriages always passes legal selection in this country. The Qur'an has provided information about interfaith marriage, namely First, surah Al-Baqarah verse 221, regarding the prohibition of Muslims marrying polytheists. Second, surah Al-Mumtahanah verse 10, regarding the prohibition of Muslims marrying infidels. Third, surah al-Maidah verse 5, regarding the prohibition of Muslim women marrying men who are people of the book and the permissibility of Muslim men marrying women who are people of the book. The main reason for the prohibition of Muslim marriages with polytheists is because of differences in faith. Because differences in faith result in no harmony. The purpose of marriage in the Qur'an, namely first to obtain peace of life, peace of mind, full of love and affection. Second, to continue or breed generations of human beings on earth or change of generations. The third is the fulfillment of sexual desires for husband and wife. The fourth is maintaining honor, namely self-respect, children and family. Fifth is worship. Therefore interfaith marriage will not achieve the goal of the marriage.